Morpho-Agronomic Diversity in Pole-Type Common Bean (Phaseolus vulgaris L.) Landraces from Lushai Hills of North-East India - S K Dutta (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2015)
The present study was based on morphological and agronomical characterization of 23 pole-type common bean (Phaseolus vulgaris L.) landraces collected from Lushai hills of North-East India. Extensive variation in plant and seed traits was found in 16 morphological and agronomical characters. Cluster analysis based on Euclidean distance grouped the genotypes into five main branches, reflecting their growth type and reproductive traits. Significant positive or negative correlation was observed among important traits. Principal component analysis was used for assessing patterns of variation by accounting for all the 10 quantitative and six qualitative variables together. Ordination among accessions showed that the first five principal components had Eigen values greater than one, and cumulatively accounted for 72% of the variation. Characterization based on quantitative and qualitative traits enabled separation of accessions into various groups representing landraces with distinct characters.